Aspek Sosiologis Tokoh Novel Cinta di Dalam Gelas Karya Andrea Hirata - Zulfitri, Afli; Thahar, Harris Effendi; Tamsin, Andria Catri (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purpose of this study was to describe the sociological aspects of the existing characters in the Cinta di Dalam Gelas by Andrea Hirata. Described the social aspects related to the social process, namely cooperation, competition, dispute or conflict, and accommodation in the novel Cinta di Dalam Gelas by Andrea Hirata. Description of the data is decomposed in the form of words and not in the form of numbers. This research is a qualitative study using descriptive methods. Sociological theory literature is mimetic approach. Data was collected by way of inventory data, including the sociological aspects of the characters in the novel Cinta di Dalam Gelas by Andrea Hirata. For data analysis techniques in this study was done by analyzing the data and a description of the data. Based on the analysis of the data can be retrieved conclusion that sociological aspects contained in the novel Cinta di Dalam Gelas by Andrea Hirata is reflected in the figures, especially prominent figures. Figures involved in the social process, namely cooperation, competition, conflict or disagreement, and accommodations. In addition, this study may be the object of teaching in the school, because learning in schools also teach literature to students.